2003
DOI: 10.1007/s00259-003-1152-y
|View full text |Cite
|
Sign up to set email alerts
|

A new animal model for the imaging of melanoma: correlation of FDG PET with clinical outcome, macroscopic aspect and histological classification in Melanoblastoma-bearing Libechov Minipigs

Abstract: The aim of this study was to evaluate the Melanoblastoma-bearing Libechov Minipigs (MeLiM) as an animal model of melanoma for in vivo imaging. Serial whole-body 2-deoxy-2-[(18)F]fluoro- d-glucose positron emission tomography (FDG PET) scans were conducted on five MeLiM. In order to explore different clinical stages of the tumoural lesions, each animal was scanned two to four times, at intervals of 30-155 days. PET images were analysed by a semiquantitative method based on the tumour to muscle metabolic ratio. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We also found that our imaging technique was a sensitive device for detecting metastasis larger than 5 mm. The in vivo monitoring of animal models with functional imaging can define disease progression or regression with dedicated PET [13] but also with DHC, when provided with a longer uptake period, as shown in our study. Various therapies modify metabolic pathways and thus FDG uptake is different prior to and after treatment.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We also found that our imaging technique was a sensitive device for detecting metastasis larger than 5 mm. The in vivo monitoring of animal models with functional imaging can define disease progression or regression with dedicated PET [13] but also with DHC, when provided with a longer uptake period, as shown in our study. Various therapies modify metabolic pathways and thus FDG uptake is different prior to and after treatment.…”
Section: Discussionmentioning
confidence: 53%
“…This may be explained by the relative lack of sensitivity and resolution of this technique, compared to dedicated PET scanners or, even more, to animal dedicated PET cameras. Animal PET scanners have a spatial resolution range of about 2 mm [10,11], while dedicated PET have a spatial resolution range of about 4Y6 mm [12,13] and DHC have a resolution of about 5 to 8 mm [14Y16]. Dedicated PET cameras and animal PET cameras also have a better detection limit because their sensitivity (in air with a line source) is 150 times greater in 3-D and 25 times greater in 2-D than DHC [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodeficient murine models allow for the study of human and murine melanomas in an immunological naive background [1719]. In addition to providing a large animal model of LNM, spontaneous swine melanoma models are used to examine practical limitations of current imaging techniques [2022]. …”
Section: Preclinical Lnm Animal Modelsmentioning
confidence: 99%
“…The MeLiM minipigs are a very suitable animal model for human melanoma due to numerous histopathological (Boisgard et al, 2003;VincentNaulleau et al, 2004) and biochemical similarities (Borovansky et al, 2003). Comparing the melanomas in the MeLiM strain and the Sinclair strain or the Munich Troll line, some resemblance exists, such as the occurrence of melanoma at birth and multiple gene inheritance Horak et al, 1999).…”
mentioning
confidence: 99%